The spending power of sub-central governments A pilot study - Bach, Steffen (OECD Working Papers on Fiscal Federalism, 2018)
This pilot study presents indicators that assess sub-central government (SCG) spending power by policy area. Traditional indicators - such as the share of SCG in total government spending - are often misleading as they underestimate the impact of central government regulation on sub-central spending patterns. In order to gauge true spending power, a set of institutional indicators is established, based on a detailed assessment of institutional, regulatory and administrative control central government exerts over various SCG policy areas. Results tend to confirm the limited discretion of SCGs over their own budget. Education in particular - the main SCG budget item in most countries - is strongly shaped by central government regulation. Federal countries tend to grant more spending power to SCGs than unitary countries